Hematological reference values for stray colony cats of northern Italy. (July 2016) - Spada, Eva; Proverbio, Daniela; Baggiani, Luciana; Canzi, Ilaria; Perego, Roberta
Abstract In additional to significant dietary, lifestyle and hormonal differences, stray cats may have different hematological parameters from pet cats. The objectives of this study are to determine hematological reference intervals (RIs) from a large population of stray cats in northern Italy, to establish whether published RIs for the general pet feline population are valid in stray cats and to evaluate the effects of age and sex on hematological parameters. Hematological data were analyzed retrospectively from the database of a trap-neuter-release program (performed in 2008–2010 in northern Italy) to generate normal RIs. RIs were determined and compared with established pet cat RIs according to the National Committee for Clinical Laboratory Standard guidelines and the American Society of Veterinary Clinical Pathology guidelines. Data from 90 healthy stray cats from 17 colonies were available for determination of hematological RIs. Based on the results of comparison with published feline RIs, new RIs were proposed for RBC count, Hct, MCV, MCHC, and WBC count in stray cats. Male cats had a statistically significant higher value than did females for RBC count (mean RBC count in females 6.5 × 1012 versus 7.4 × 1012 /L in males, P  = 0.001), Hb (mean Hb concentration in females 9.9 versus 10.9 g/dL in males, P  = 0.004), and Hct (mean Hct in females 24.8 versus 28.2 % in males, P  = 0.001). Significant differences in five hematological parameters were found between stray and pet cats, for most of which the most plausible explanation is probably anesthetic effect and infections or parasitism. It can therefore be assumed that there is no need to establish a specific RI for most of the CBC variables in stray cats.